Third trimester amniocentesis for diagnosis of inherited bleeding disorders prior to delivery. (6th August 2013) - Cutler, J.; Chappell, L. C.; Kyle, P.; Madan, B.
Summary: X‐linked and autosomally inherited bleeding disorders confer a risk of foetal intracranial haemorrhage during delivery. Conventional prenatal diagnosis involving chorionic villus sampling or early amniocentesis is primarily aimed at offering the choice of pregnancy termination. Currently, non‐invasive procedures, involving analysis of free foetal DNA in the maternal circulation, are restricted to gender determination, and are of limited value in women at risk of carrying a foetus with a bleeding disorder. These limitations, together with the rising proportion of women shown to be carrying an affected foetus, who decide to continue the pregnancy, have led to the development of prenatal mutation identification via late amniocentesis after 34 weeks of gestation, with the sole aim of directing delivery management. Although this approach has been documented in some cases of potential foetal anomaly, there are no previous reports of its use in women with heritable bleeding disorders. We report a single‐centre experience of this technique in managing nine such deliveries. Of these, three showed an affected foetus, five showed an unaffected foetus and in one case no result could be obtained. In the three affected cases and the one with the inconclusive result restrictive birth plans were implemented, whereas the five unaffected cases underwent routine obstetric management; with one delivery necessitating interventions which would have been contraindicated if foetal status had not been determined. Late amniocentesis is a safe technique for guiding delivery management in women with bleeding disorders where the mutation is known.